Mechanistic Insights into the Role of Atg11 in Selective Autophagy. Issue 1 (3rd January 2020) - Zientara-Rytter, Katarzyna; Subramani, Suresh
Abstract: Macroautophagy (referred to hereafter as autophagy) is an intracellular degradation pathway in which the formation of a double-membrane vesicle called the autophagosome is a key event in the transport of multiple cytoplasmic cargo (e.g., proteins, protein aggregates, lipid droplets or organelles) to the vacuole (lysosome in mammals) for degradation and recycling. During this process, autophagosomes are formed de novo by membrane fusion events leading to phagophore formation initiated at the phagophore assembly site. In yeast, Atg11 and Atg17 function as protein scaffolds, essential for selective and non-selective types of autophagy, respectively. While Atg17 functions in non-selective autophagy are well-defined in the literature, less attention is concentrated on recent findings regarding the roles of Atg11 in selective autophagy. Here, we summarize current knowledge about the Atg11 scaffold protein and review recent findings in the context of its role in selective autophagy initiation and autophagosome formation. Graphical Abstract: Unlabelled Image Highlights: Atg11 is a critical protein for selective autophagy. Atg11 serves as a platform for the recruitment of the core autophagic machinery and a hub for numerous protein–protein interactions during selective autophagy. Atg11 coordinates several steps of selective autophagy from cargo selection and PAS organization to autophagosome maturation and the termination of selective autophagy. Atg11 scaffold has functional counterparts in higher eukaryotes.